Digitalization of CDC Environmental Communication in Handling Ciliwung River Ecosystem Sustainability through Instagram - Nurdiansyah, Dian; Maharani, Melody A; Kamiliya, Shafa; Musyafa, Febriyanti (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Digitalization technology has brought significant changes to people's lives. Environmental communication in the current era is present due to the emerging concerns regarding environmental damage and climate change that are increasingly evident worldwide. The Ciliwung watershed, which stretches long and passes through major cities in Indonesia, is, in fact, currently in a condition where its environmental ecosystem is increasingly crowded with piles of garbage, landfills, and wastewater pollution from irresponsible industries. The presence of the Instagram platform as a medium for environmental communication provides a significant opportunity for communities or organizations to continue campaigning on environmental issues, such as the Ciliwung Depok Community (CDC). The research conducted by the researcher aims to analyze and find forms of environmental communication as part of the CDC's efforts to deal with the preservation of river ecosystems through the Instagram platform. The research used a qualitative method with data collection conducted using virtual observation techniques and semi-structured interviews with several influential figures in the community and society. Data analysis in this study uses the Miles and Huberman, an interactive technique; the data will later be validated using source triangulation. The results show that CDC is able to become a community that conveys messages of conservation and education of the Ciliwung River ecosystem to its audience utilizing the Instagram Social Media platform. Communicating using Instagram allows users (CDC) to continue to represent community identity, communicate, collaborate, and interact with users so as to build social ties online. Thus, as a digital communication platform, Instagram is a very important tool in environmental conservation and sustainable development efforts, especially in the Ciliwung River ecosystem.